A Community-Based Investigation of Stigma Toward Individuals Receiving Methadone Maintenance Treatment in China: A Randomized Case Vignette Study - Deng, Qijian; Hu, Maorong; Yu, Fang; Liu, Qiaosheng; Hao, Wei; Wu, Qiuxia; Luo, Tao (Frontiers in Psychiatry, 2020)
Background: Even though methadone maintenance treatment (MMT) is effective and widely recommended, it is widely misunderstood and stigmatized. This study aimed to explore people's attitudes and beliefs toward MMT, and stigmatization of MMT patients in China. Methods: This randomized, vignette-based study enrolled 1,066 household respondents (552 males and 514 females, response rate is 88.83%, 86.00% in vignette 1 and 91.66% in vignette 2) from two communities in China. Respondents initially completed questionnaires on sociodemographic characteristics and their knowledge about methadone and MMT. They were then randomly assigned to vignette 1 (described a patient receiving MMT) or vignette 2 (described a patient receiving amlodipine treatment). The labeling, stereotyping, and social distance toward the individual described in the vignettes were evaluated. Results: In these two vignettes, respondents showed a significantly higher level of stigma and discrimination toward the patient receiving MMT than the patient receiving amlodipine treatment. Approximately 60% of respondents believed that methadone is a type of addictive drug and that participating in MMT is a way to get high. Over 60% of respondents labeled the heroin-dependent patient who is receiving MMT as an addict even though the patient has not used heroin for several years; about 80% of them believed that the patient has undesirable characteristics and expressed a strong desire for social distance. Conclusions: People's misunderstanding of MMT, and stigmatization of MMT patients were very common among populations in the communities in China. To maximize MMT patients benefiting from MMT programs, more efforts are needed to minimize the impact of MMT-related stigma.